Mini Workshop on a Bicycle - Bhattacharyya, P.K. (SCHOOL SCIENCE, 2013)
Some basic hand-tools and simple machine tools are required for developing prototypes, maintaining equipment, making models for hobby centres and even for day-to-day household repairs. Those who like to enjoy the charm of working with their own hands often face the problem of grinding, turning, facing, coil winding, drilling, etc. These are very common operations required for a small job. School children generally work on light sheet metals and wood (which can be easily fabricated) while making their own models. They also require similar operations to be done on those. Those who are to set up models on electricity (low voltage) will not like to work with torch cells if other source of electricity is available. This is due to various difficulties with the torch cells. Schools and hobby centres having electricity supply can use motorised units for fabrication works. For a typical rural situations, we then have to think of some mechanically driven implements. For designing school science equipment, we have encouraged the use of common indigenous materials which are available everywhere. The power, generated at the bicycle pedals, can solve some of those problems nicely. Bicycle is available everywhere. Only some attachments are to be fitted in it to serve the purpose